Measurement of the ratio of branching fractions B(B+c→J/[psi]K+)/B(B+c→J/[psi]π+) - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2016)
The ratio of branching fractions RK/π≡B(B+c→J/ψK+)/B(B+c→J/ψπ+) is measured with pp collision data collected by the LHCb experiment at centre-of-mass energies of 7 TeV and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. It is found to be R K/π = 0.079 ± 0.007 ± 0.003, where the first uncertainty is statistical and the second is systematic. This measurement is consistent with the previous LHCb result, while the uncertainties are significantly reduced.